PEMBELAJARAN MUSIK IRINGAN TARI KABELA MELALUI MODEL PEMBELAJARAN DIRECT INSTRUCTION DI KELAS XI IPA 1 SMA NEGERI 2 KOTAMOBAGU - Muhammad Rafii Sardi; La Ode Karlan; Mimy A. Pulukadang; Rahmawati Ohi; Riana Diah Sitharesmi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the effectiveness of applying the Direct Instruction learning model in teaching musical accompaniment for the Kabela dance at SMA Negeri 2 Kotamobagu. The focus of the research is to determine the extent to which this model can improve students’ skills in playing musical instruments for dance accompaniment and to identify the challenges encountered during the learning process. This research employed a qualitative approach using observation, interviews, and documentation methods. The subjects of the study were students involved in learning musical accompaniment for the dance at the school. The results showed that the implementation of the Direct Instruction model significantly helped students understand and play accompanying musical instruments, such as the flute, tambourine, and gong. Systematic learning through the stages of introduction, material presentation, guided practice, independent practice, and evaluation made it easier for students to understand the rhythm and tempo patterns of the Kabela dance accompaniment. The main challenges found in this study were students’ difficulties in synchronizing tempo in group performances and their lack of prior experience in playing traditional musical instruments. However, these challenges could be minimized through regular practice and intensive guidance from the teacher during the learning process. In conclusion, the study finds that the Direct Instruction learning model is effective in improving students’ skills in playing musical accompaniment for the Kabela dance. This model can serve as an alternative method in music education at schools to enhance students’ understanding and skills in a systematic and structured way.